2010
DOI: 10.1371/journal.pgen.1000829
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary Mirages: Selection on Binding Site Composition Creates the Illusion of Conserved Grammars in Drosophila Enhancers

Abstract: The clustering of transcription factor binding sites in developmental enhancers and the apparent preferential conservation of clustered sites have been widely interpreted as proof that spatially constrained physical interactions between transcription factors are required for regulatory function. However, we show here that selection on the composition of enhancers alone, and not their internal structure, leads to the accumulation of clustered sites with evolutionary dynamics that suggest they are preferentially… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
67
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(73 citation statements)
references
References 41 publications
(51 reference statements)
6
67
0
Order By: Relevance
“…Within a promoter, complex binding-site patterns like clustering, which were once thought to be adaptive, may in fact emerge from neutral evolution (23). At the subgraph level, commonly accepted motifs are poorly conserved across homologous genes (24); thus, convergent evolution of subgraphs (24, 25) is more simply explained as the result of neutral forces acting similarly in divergent species rather than as an adaptive response to environmental changes.…”
Section: Discussionmentioning
confidence: 99%
“…Within a promoter, complex binding-site patterns like clustering, which were once thought to be adaptive, may in fact emerge from neutral evolution (23). At the subgraph level, commonly accepted motifs are poorly conserved across homologous genes (24); thus, convergent evolution of subgraphs (24, 25) is more simply explained as the result of neutral forces acting similarly in divergent species rather than as an adaptive response to environmental changes.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, we found that loss of a TATA box at enhancer iHMRs predicts loss of hypomethylation in chimp, suggesting a role for TBP and the transcriptional machinery, in addition to the function of other specific TFs, in the establishment of these iHMRs. These comparisons may thus serve to distinguish those enhancer iHMRs that fit an ''enhanceosome'' model, whereby exclusion of a single binding event can wipe out enhancer function in one species (possibly by loss of hypomethylation), or a ''billboard'' model in which bindingsite rearrangements within the enhancer are tolerated as long as the sum of TF interaction is constant (Arnosti and Kulkarni 2005;Lusk and Eisen 2010).…”
Section: Org Downloaded Frommentioning
confidence: 99%
“…In one study to focus on the effects of purifying selection and regulatory function, Lusk and Eisen (2010) simulated enhancer evolution using binding site composition as the measure of fitness. They considered the case in which having too few TF binding sites is lethal and all alleles above the threshold number of binding sites are functionally equivalent (Lusk and Eisen 2010).…”
mentioning
confidence: 99%
“…They considered the case in which having too few TF binding sites is lethal and all alleles above the threshold number of binding sites are functionally equivalent (Lusk and Eisen 2010). The authors required a binary classification of sequence into what is or is not a binding site.…”
mentioning
confidence: 99%
See 1 more Smart Citation